A first-principles study on three-dimensional covalently-bonded hexagonal boron nitride nanoribbons. (28th January 2015) - Lee, Sang-Hoon; Jhi, Seung-Hoon
Abstract: We studied three-dimensional honeycomb-structure boron nitride (BN) allotrope using first-principles calculations and the tight-binding method. Interconnected by sp 3 -bonding at the vertices, hexagonal BN nanoribbons construct highly-porous, covalently-bonded hexagonal BN nanoribbons (CBBNs). We investigated the structural and mechanical properties of CBBNs with various sizes, compared with those of carbon and other BN allotropes. The mechanical and thermal stabilities are also checked. Our calculations show that, despite the high porosity and low mass density, CBBNs are stable and mechanically hard materials as cubic BN. Moreover, our calculated results suggest that CBBNs can be regarded as a binary alloy of sp 2 - and sp 3 -bonded BNs following the Vegard's rule in average bond lengths and bulk moduli. Calculated band structures show that the band gap of CBBNs has similar variation upon increasing size as BN nanoribbons and is also limited by the second-neighbor interaction between the p z states of sp 2 -bonded atoms in adjacent nanoribbons.